Bahaya Zat Aditif Dalam Makanan Ringan Anak- Anak - Jelita, Jelita; Nuraida, Nuraida; Utari, Ade Paramitha (azkiya, 2024)
This article aims to determine the response of parents and traders to the harmful of additives contained in children's snacks and the efforts made to overcome them. The method used is descriptive qualitative with research subjects as many as 30 parents and 7 traders who are in the TPQ environment of the Great Mosque of Darul Falah Langsa, Aceh. Data were collected through interviews and questionnaires. The results showed that parents understand about the harmful that will be faced by children if they consume snacks that contain additives in snacks. However, parents cannot fully control their children's activities outside the home and often get stomachaches and allergies. Efforts are being made to reduce pocket money and provide understanding to their children. According to merchant, the ingredients added to snacks are dyes, flavourings, sweeteners, and preservatives and understand the impact of giving these additives. The addition of these additives does not follow the established rules, but is in accordance with the wishes of the merchant. Thus, excessive use of additives can be disastrous for children, and both parents and traders are aware of the impacts caused by excessive use of these additives.